Pellet, and molded article
The use of a resin composition with polycarbonate resin, titanium oxide particles, and phosphate in pellets addresses the challenge of hue stability and discoloration in polycarbonate resin reflective members, achieving enhanced heat resistance and color stability in molded products.
Patent Information
- Application Number
- JP2023147793
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-25
AI Technical Summary
Polycarbonate resin used as a reflective member requires high hue stability and suppression of discoloration after heat resistance testing.
A resin composition containing polycarbonate resin, titanium oxide particles, and phosphate, where the titanium oxide particles have a silicon-containing compound, organosiloxane, or aluminum compound on their surface, and the phosphate is an inorganic phosphate or a phosphate salt with a pH of less than 7.0, is used to create pellets that form molded products with enhanced heat resistance and color stability.
The described composition effectively suppresses discoloration in molded products after heat resistance testing, maintaining high hue stability and improving the physical properties of the materials.
Smart Images

Figure 2025040778000001 
Figure 2025040778000002 
Figure 2025040778000003
Abstract
Description
[Technical field]
[0001] The present invention relates to pellets and molded articles, and in particular to pellets containing a polycarbonate resin. [Background technology]
[0002] Polycarbonate resin is a general-purpose engineering plastic that has excellent transparency, mechanical strength, electrical properties, heat resistance, and dimensional stability, and is therefore used in a wide range of fields, including electrical and electronic equipment parts, office equipment, machine parts, vehicle parts, building materials, various containers, and leisure goods and miscellaneous goods.
[0003] One of the applications of polycarbonate resins is optical members such as light guide plates (Patent Document 1, Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-59150 A [Patent Document 2] JP 2000-198916 A Summary of the Invention [Problem to be solved by the invention]
[0005] When polycarbonate resin is used for a reflective member, it is required to have a high level of hue, and in particular, it is required to suppress discoloration after a heat resistance test to a high degree. The present invention has an object to solve the above problems, and to provide pellets capable of providing molded articles that can be highly inhibited from discoloring after a heat resistance test, and a molded article. [Means for solving the problem]
[0006] In view of the above problems, the present inventors have conducted research and found that the above problems can be solved by blending a phosphate with a resin composition containing a polycarbonate resin and titanium oxide particles. Specifically, the above problems were solved by the following means. <1> For 100 parts by mass of polycarbonate resin (A), Titanium oxide particles (B) of more than 0.1 parts by mass and not more than 30 parts by mass, Contains 0.005 to 0.5 parts by mass of phosphate (C), Pellets of a resin composition. <2> The titanium oxide particles (B) contain a silicon-containing compound on the surface thereof. <1> 2. Pellets of the resin composition according to claim 1. <3> The titanium oxide particles (B) contain organosiloxane on the surface. <1> 2. Pellets of the resin composition according to claim 1. <4> The titanium oxide particles (B) contain an aluminum compound on the surface thereof. <1> ~ <3> A pellet of the resin composition according to any one of the above. <5> The titanium oxide particles (B) contain organosiloxane and an aluminum compound on the surface thereof. <1> 2. Pellets of the resin composition according to claim 1. <6> The phosphate (C) comprises an inorganic phosphate; <1> ~ <5> 2. A pellet of the resin composition according to claim 1. <7> The phosphate (C) comprises a phosphate having a pH of less than 7.0; <1> ~ <6> 2. A pellet of the resin composition according to claim 1. <8> The phosphate (C) comprises sodium dihydrogen phosphate or / and potassium dihydrogen phosphate; <1> ~ <7> 2. A pellet of the resin composition according to claim 1. <9> The titanium oxide particles (B) contain an organosiloxane and an aluminum compound on the surface, and the phosphate (C) contains sodium dihydrogen phosphate and / or potassium dihydrogen phosphate. <1> ~ <8> 2. A pellet of the resin composition according to claim 1. <10> For light guide plates, <1> ~ <9> 2. A pellet of the resin composition according to claim 1. <11> <1> ~ <10> 2. A molded article formed from pellets of the resin composition according to claim 1. Effect of the Invention
[0007] According to the present invention, it is possible to provide pellets capable of producing molded articles capable of suppressing discoloration after a heat resistance test to a high level, and a molded article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values are those at 23° C. unless otherwise specified. If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated.
[0009] The pellets of this embodiment are characterized in that they are pellets of a resin composition containing more than 0.1 part by mass and 30 parts by mass or less of titanium oxide particles (B) and 0.005 to 0.5 parts by mass of a phosphate (C) relative to 100 parts by mass of a polycarbonate resin (A). By adopting such a constitution, pellets are obtained that can provide a molded product that can suppress discoloration after a heat resistance test to a high level. The surface of the titanium oxide particles (B) may have exposed reactive hydroxyl groups. Such hydroxyl groups damage the polycarbonate resin (A). The titanium oxide particles (B) may be surface-treated, but are usually surface-treated in the form of secondary particles. Therefore, when a shear force is applied, the titanium oxide particles (B) become primary particles, and some of the hydroxyl groups of the titanium oxide particles (B) are exposed on the surface. In this embodiment, it is presumed that the phosphate ions in the phosphate (C) act on the hydroxyl groups exposed on the surface of the titanium oxide particles (B), thereby minimizing damage to the polycarbonate resin (A). The resin composition used in the pellets of this embodiment will be described below.
[0010] <Polycarbonate resin (A)> The resin composition used in the present embodiment contains a polycarbonate resin (A). Specifically, the polycarbonate resin (A) is not particularly limited as long as it contains a -[OR-OC(=O)]- unit (wherein R is an organic group, preferably a hydrocarbon group, more preferably an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and further has a straight-chain structure or a branched structure) containing a carbonate bond in the molecular main chain. In this embodiment, the polycarbonate resin (A) is preferably an aromatic polycarbonate resin, more preferably a polycarbonate resin having a bisphenol skeleton, and more preferably at least one of bisphenol A type polycarbonate resin, bisphenol C type polycarbonate resin, and bisphenol AP type polycarbonate resin, and more preferably a bisphenol A type polycarbonate resin. By using such a polycarbonate resin, better heat resistance and toughness can be achieved. In the present embodiment, the polycarbonate resin having a bisphenol skeleton preferably contains, of all structural units, 90 mol % or more of structural units having a bisphenol skeleton (preferably structural units having a bisphenol A type skeleton), and more preferably contains, of all structural units, 95 mol % or more of structural units having a bisphenol skeleton.
[0011] The viscosity average molecular weight (Mv) of the polycarbonate resin (A) is preferably 10,000 or more, more preferably 12,000 or more, even more preferably 13,000 or more, and even more preferably 14,000 or more. By making it equal to or more than the lower limit, the durability of the molded article obtained tends to be further improved. The upper limit of the viscosity average molecular weight (Mv) of the polycarbonate resin (A) is preferably 25,000 or less, more preferably 22,000 or less. By making it equal to or less than the upper limit, the molding processability of the molded article tends to be further improved. The viscosity average molecular weight (Mv) was calculated by using methylene chloride as a solvent and an Ubbelohde viscometer to determine the intrinsic viscosity [η] (unit: dL / g) at 25°C, and then using the Schnell viscosity formula, i.e., η = 1.23 × 10 -4 ×Mv 0.83 , means a value calculated from When two or more types of polycarbonate resins are used, the viscosity average molecular weight is the mixture.
[0012] The method for producing the polycarbonate resin (A) is not particularly limited, and polycarbonate resins produced by the conventionally known phosgene method (interfacial polymerization method) or melting method (ester exchange method) can be used. When the melting method is used, a polycarbonate resin having an adjusted amount of OH groups at the terminal groups can be used.
[0013] The polycarbonate resin (A) used in this embodiment may be a recycled polycarbonate resin product (including recovered products, material recycled products, chemical recycled products, etc.), a rejected product, or a scrap from the molding of a thermoplastic resin.
[0014] In addition to the above, details of the polycarbonate resin (A) can be referred to in paragraphs 0013 to 0041 of JP 2021-084942 A and in paragraphs 0030 to 0035 of JP 2021-119211 A, the contents of which are incorporated herein by reference.
[0015] The proportion of the polycarbonate resin (A) in the resin composition used in this embodiment is preferably 70% by mass or more, more preferably 75% by mass or more, even more preferably 80% by mass or more, and even more preferably 83% by mass or more. By making it equal to or more than the lower limit, the impact resistance of the obtained molded article tends to be further improved. In addition, the proportion of the polycarbonate resin (A) in the resin composition used in this embodiment is preferably 95% by mass or less, more preferably 90% by mass or less. By making it equal to or less than the upper limit, the light blocking property of the obtained molded article tends to be further improved. The resin composition used in the present embodiment may contain only one type of polycarbonate resin (A), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0016] <Titanium oxide particles (B)> The resin composition used in the present embodiment contains titanium oxide particles (B). By containing titanium oxide particles (B), it is possible to impart color to the obtained molded product, increase the whiteness, and achieve light-shielding properties. The titanium oxide particles (B) are usually the particles with the highest titanium oxide content, and the proportion of titanium oxide in the titanium oxide particles (B) is 85.0 mass% or more, preferably 90.0 mass% or more. The upper limit of the proportion of titanium oxide in the titanium oxide particles (B) is usually less than 100 mass%, preferably 99.9 mass% or less.
[0017] The titanium oxide particles (B) more preferably contain a silicon-containing compound on the surface, further preferably contain an organosiloxane, and even more preferably contain a polyorganosiloxane. In addition, the titanium oxide particles (B) preferably contain an aluminum compound on the surface. In this embodiment, it is particularly preferable that the titanium oxide particles (B) contain an organosiloxane and an aluminum compound on the surface. By using such titanium oxide (B), discoloration of the obtained molded article after a heat resistance test can be suppressed to a higher level. Such titanium oxide particles (B) are usually obtained by treating the surface with a surface treatment agent. Therefore, the surface treatment agent preferably contains at least one of Al2O3, Al(OH)3, and SiO2, and more preferably contains Al2O3, Al(OH)3, and SiO2. The surface treatment agent may be physically adsorbed or chemically bonded to the titanium oxide surface.
[0018] The titanium oxide particles (B) preferably contain silicon dioxide, more preferably in an amount of 0.50% by mass or more, and more preferably in an amount of 4.5% by mass or less. The titanium oxide particles (B) preferably contain aluminum oxide in a proportion of 1.50% by mass or more, and preferably in a proportion of 4.50% by mass or less. The silicon oxide and aluminum oxide in the titanium oxide particles (B) are values calculated by measuring with fluorescent X-ray analysis and converting them into oxides. Specifically, they are evaluated by semi-quantitative measurement. The total of oxides is taken as 100 mass%, and the ratio (mass%) of each metal converted into an oxide is used. For the measurement, ZSX Primus manufactured by Rigaku Corporation can be used. Details are measured according to the description of the examples described later.
[0019] In this embodiment, the titanium oxide particles (B) may be either rutile type titanium oxide particles or anatase type titanium oxide particles. The titanium oxide is usually titanium dioxide.
[0020] In this embodiment, the resin composition contains more than 0.1 parts by mass and not more than 30 parts by mass of titanium oxide particles (B) per 100 parts by mass of polycarbonate resin (A). By making it not more than the upper limit, the effect of suppressing deterioration of physical properties tends to be further improved. Also, by making it not less than the lower limit, the effect of improving light blocking properties tends to be further improved. In this embodiment, the content of the titanium oxide particles (B) is preferably 1.0 part by mass or more, more preferably 7.0 parts by mass or more, and even more preferably 11.0 parts by mass or more, relative to 100 parts by mass of the polycarbonate resin (A). In this embodiment, the content of the titanium oxide particles (B) is preferably 25 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 18 parts by mass or less, and even more preferably 15 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin (A). The resin composition used in the present embodiment may contain only one type of titanium oxide particles (B), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0021] <Phosphate (C)> The resin composition used in this embodiment contains a phosphate (C). It is presumed that the phosphate (C) reacts with the hydroxyl groups exposed on the surface of the titanium oxide (B) to make the polycarbonate resin (A) less susceptible to damage. The phosphate (C) may be an organic phosphate or an inorganic phosphate, but is preferably an inorganic phosphate. The phosphate (C) is also preferably a weakly acidic salt, more preferably a weakly acidic phosphate. The pH of the phosphate (C) used in this embodiment is preferably less than 7.0, more preferably 6.5 or less, even more preferably 6.0 or less, even more preferably 5.5 or less, even more preferably 5.0 or less, even more preferably 4.8 or less, and preferably 2.0 or more, more preferably 3.0 or more, and even more preferably 4.0 or more. By using a phosphate with a pH of less than 7.0, heat-resistant discoloration can be more effectively suppressed. If the phosphate (C) is not soluble in water, dissolve it in a water-miscible or water-immiscible solvent and measure the pH. If a water-miscible solvent is used, measure the pH by immersing the electrode in the mixture. If a water-immiscible solvent is used, measure the pH after solvent extraction of the sample in the aqueous phase using deionized water.
[0022] The phosphate (C) used in the present embodiment is exemplified by sodium dihydrogen phosphate and / or potassium dihydrogen phosphate, and is preferably sodium dihydrogen phosphate. The phosphate (C) may be a hydrate.
[0023] The content of the phosphate (C) in the resin composition used in this embodiment is 0.005 parts by mass or more, preferably 0.008 parts by mass or more, more preferably 0.01 parts by mass or more, even more preferably 0.05 parts by mass or more, and even more preferably 0.07 parts by mass or more, relative to 100 parts by mass of the polycarbonate resin (A). The content of the phosphate (C) is 0.5 parts by mass or less, preferably 0.40 parts by mass or less, more preferably 0.30 parts by mass or less, even more preferably 0.24 parts by mass or less, and even more preferably 0.22 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin (A). By making it equal to or more than the lower limit, the effect of protecting the active surface of titanium oxide tends to be further improved. Also, by making it equal to or less than the upper limit, the decomposition of the polycarbonate resin can be effectively suppressed.
[0024] The content of the phosphate (C) in the resin composition used in this embodiment is preferably 0.001 mass% or more, more preferably 0.003 mass% or more, and even more preferably 0.08 mass% or more, and is preferably 0.3 mass% or less, and more preferably 0.25 mass% or less. The resin composition used in this embodiment may contain only one type of phosphate (C), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range. When the phosphate (C) is a hydrate, the amount of the phosphate (C) is the amount of the phosphate including the hydrate.
[0025] <Other ingredients> The resin composition used in the present embodiment may contain other components as necessary, as long as the desired physical properties are not significantly impaired. Examples of the other components include reinforcing materials, thermoplastic resins other than polycarbonate resins, and various resin additives. Regarding the reinforcing material, the description in paragraphs 0107 to 0115 of JP 2014-136710 A can be referred to, the contents of which are incorporated herein by reference. Examples of resin additives include flame retardants (particularly alkali metal salts), elastomers, stabilizers, release agents, reactive compounds (epoxy compounds, etc.), colorants (dyes, pigments), antistatic agents, UV inhibitors, anti-fogging agents, anti-blocking agents, flow improvers, plasticizers, dispersants, antibacterial agents, etc. The resin additives may be contained alone or in any combination and ratio of two or more. Regarding resin additives, the description in paragraphs
[0117] to
[0128] of JP2015-117298A can be referred to, the contents of which are incorporated herein by reference.
[0026] <<Flame retardants>> The resin composition used in this embodiment may contain a flame retardant. As the flame retardant, silicone-based flame retardants, alkali metal salts and phosphorus-based flame retardants are preferred, with alkali metal salts being more preferred.
[0027] As the silicone-based flame retardant, polyorganosiloxane is preferable. For other details of the silicone-based flame retardant, the description in paragraphs 0075 to 0082 of the specification of Japanese Patent No. 6285085 can be referred to, and the contents thereof are incorporated herein by reference. Examples of the alkali metal salt include metal sulfonates, metal carboxylates, metal borates, and metal phosphates, with metal sulfonates being preferred from the standpoint of thermal stability.
[0028] Examples of metals constituting the alkali metal salt include lithium (Li), sodium (Na), potassium (K), rubidium (Rb), and cesium (Cs). Of these, sodium, potassium, and cesium are preferred, and sodium and potassium are more preferred.
[0029] Preferred examples of the alkali metal sulfonate include alkali metal salts of fluorine-containing aliphatic sulfonic acids or aromatic sulfonic acids. Specific examples of preferred ones among them include alkali metal salts of fluorine-containing aliphatic sulfonic acids having at least one C—F bond in the molecule, such as potassium perfluorobutanesulfonate, lithium perfluorobutanesulfonate, sodium perfluorobutanesulfonate, cesium perfluorobutanesulfonate, potassium trifluoromethanesulfonate, lithium trifluoromethanesulfonate, sodium trifluoromethanesulfonate, and cesium trifluoromethanesulfonate; dipotassium diphenylsulfone-3,3′-disulfonate, potassium diphenylsulfone-3-sulfonate, sodium benzenesulfonate, and sodium (poly)styrenesulfonate. Examples of aromatic sulfonate alkali metal salts having at least one aromatic group in the molecule include sodium paratoluenesulfonate, sodium (branched)dodecylbenzenesulfonate, sodium trichlorobenzenesulfonate, potassium benzenesulfonate, potassium styrenesulfonate, (poly)potassium styrenesulfonate, potassium paratoluenesulfonate, potassium (branched)dodecylbenzenesulfonate, potassium trichlorobenzenesulfonate, cesium benzenesulfonate, (poly)cesium styrenesulfonate, cesium paratoluenesulfonate, cesium (branched)dodecylbenzenesulfonate, and cesium trichlorobenzenesulfonate.
[0030] For other alkali metal salts, refer to paragraphs 0069 to 0078 of JP2015-117298A, the contents of which are incorporated herein by reference.
[0031] The content of the alkali metal salt in the resin composition used in this embodiment is preferably 0.005 parts by mass or more, more preferably 0.008 parts by mass or more, even more preferably 0.01 parts by mass or more, even more preferably 0.03 parts by mass or more, and even more preferably 0.05 parts by mass or more, relative to 100 parts by mass of the (A) polycarbonate resin. By making it equal to or more than the lower limit, the formation of a carbonized layer during combustion of the polycarbonate resin can be promoted, and the flame retardancy can be further improved. In addition, the content of the alkali metal salt is preferably 1 part by mass or less, more preferably 0.8 parts by mass or less, even more preferably 0.5 parts by mass or less, even more preferably 0.3 parts by mass or less, even more preferably 0.2 parts by mass or less, and even more preferably 0.15 parts by mass or less, relative to 100 parts by mass of the (A) polycarbonate resin. By making it equal to or less than the upper limit, the flame retardant effect tends to be more effectively exhibited, despite the reduction in the content of the flame retardant. The resin composition used in the present embodiment may contain only one type of alkali metal salt, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0032] <<Elastomer>> The resin composition used in the present embodiment also preferably contains an elastomer. The elastomer is preferably a copolymer obtained by graft-copolymerizing a rubber component with a monomer component copolymerizable therewith. The method for producing such a graft copolymer may be any of bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc., and the copolymerization method may be one-stage grafting or multi-stage grafting.
[0033] The rubber component has a glass transition temperature of usually 0° C. or less, preferably −20° C. or less, and more preferably −30° C. or less. Specific examples of the rubber component include polybutadiene rubber, polyisoprene rubber, polyalkyl acrylate rubber such as polybutyl acrylate, poly(2-ethylhexyl acrylate), and butyl acrylate-2-ethylhexyl acrylate copolymer, silicone rubber such as organopolysiloxane rubber, butadiene-acrylic composite rubber, IPN type composite rubber consisting of organopolysiloxane rubber and polyalkyl acrylate rubber, styrene-butadiene rubber, ethylene-α-olefin rubber such as ethylene-propylene rubber, ethylene-butene rubber, and ethylene-octene rubber, ethylene-acrylic rubber, and fluororubber. These may be used alone or in combination of two or more. Among these, polybutadiene rubber, polyalkyl acrylate rubber, IPN type composite rubber consisting of organopolysiloxane rubber and polyalkyl acrylate rubber, and styrene-butadiene rubber are preferred from the standpoint of mechanical properties and surface appearance.
[0034] Specific examples of the monomer component that can be graft-copolymerized with the rubber component include aromatic vinyl compounds, vinyl cyanide compounds, (meth)acrylic acid ester compounds, (meth)acrylic acid compounds, epoxy group-containing (meth)acrylic acid ester compounds such as glycidyl (meth)acrylate; maleimide compounds such as maleimide, N-methylmaleimide, and N-phenylmaleimide; α,β-unsaturated carboxylic acid compounds such as maleic acid, phthalic acid, and itaconic acid, and their anhydrides (e.g., maleic anhydride, etc.). These monomer components may be used alone or in combination of two or more. Among these, from the standpoint of mechanical properties and surface appearance, aromatic vinyl compounds, vinyl cyanide compounds, (meth)acrylic acid ester compounds, and (meth)acrylic acid compounds are preferred, and (meth)acrylic acid ester compounds are more preferred. Specific examples of the (meth)acrylic acid ester compounds include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, and octyl (meth)acrylate.
[0035] The elastomer used in this embodiment is preferably a core / shell type graft copolymer type in terms of impact resistance and surface appearance. Among them, a core / shell type graft copolymer is preferred, which is made of at least one rubber component selected from polybutadiene-containing rubber, polybutyl acrylate-containing rubber, and IPN-type composite rubber made of organopolysiloxane rubber and polyalkyl acrylate rubber as a core layer, and a shell layer formed by copolymerizing (meth)acrylic acid ester around the core layer, and in particular, a core / shell type elastomer with a butadiene-based rubber as a core is preferred. In the above-mentioned core / shell type graft copolymer, one containing 40% by mass or more of the rubber component is preferred, and one containing 60% by mass or more is more preferred. Also, one containing 10% by mass or more of the (meth)acrylic acid component is preferred.
[0036] Preferable specific examples of these core / shell type graft copolymers include acrylonitrile-butadiene-styrene copolymers (ABS), methyl methacrylate-butadiene-styrene copolymers (MBS), methyl methacrylate-acrylonitrile-butadiene-styrene copolymers (MABS), methyl methacrylate-butadiene copolymers (MB), methyl methacrylate-acrylic rubber copolymers (MA), methyl methacrylate-acrylic rubber-styrene copolymers (MAS), methyl methacrylate-acrylic-butadiene rubber copolymers, methyl methacrylate-(acrylic-silicone IPN rubber) copolymers, polybutyl acrylate-acrylate copolymers, etc. Such rubbery polymers may be used alone or in combination of two or more. In addition to the above, as the elastomer, those described in paragraphs 0068 to 0079 of JP 2019-123809 A can be used, the contents of which are incorporated herein by reference.
[0037] When the resin composition used in this embodiment contains an elastomer, the content thereof is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and even more preferably 1.5 parts by mass or more, relative to 100 parts by mass of the (A) polycarbonate resin. By making the content equal to or more than the lower limit, the impact resistance of the obtained molded article tends to be improved. In addition, the upper limit of the content of the elastomer is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, even more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, relative to 100 parts by mass of the (A) polycarbonate resin. By making the content equal to or less than the upper limit, the surface hardness, heat resistance, rigidity, etc. of the obtained molded article tend to be improved. In addition, the flame retardancy also tends to be improved. The resin composition used in the present embodiment may contain only one type of elastomer, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0038] <<Stabilizer>> The stabilizers include heat stabilizers and antioxidants. Examples of the stabilizer include phenol-based, amine-based, phosphorus-based, and thioether-based stabilizers. Among them, in the present embodiment, phosphorus-based heat stabilizers and / or phenol-based antioxidants are preferred, and phosphorus-based heat stabilizers are more preferred.
[0039] Any known phosphorus-based heat stabilizer can be used. Specific examples include phosphorus oxoacids such as phosphoric acid, phosphonic acid, phosphorous acid, phosphinic acid, and polyphosphoric acid; metal acid pyrophosphates such as sodium acid pyrophosphate, potassium acid pyrophosphate, and calcium acid pyrophosphate; phosphates of Group 1 or Group 2B metals such as potassium phosphate, sodium phosphate, cesium phosphate, and zinc phosphate; organic phosphate compounds, organic phosphite compounds, and organic phosphonite compounds, with organic phosphite compounds being particularly preferred.
[0040] Examples of organic phosphite compounds include triphenyl phosphite, tris(mononylphenyl)phosphite, tris(mononyl / dinonyl phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyl diphenyl phosphite, dioctyl monophenyl phosphite, monodecyl diphenyl phosphite, didecyl monophenyl phosphite, tridecyl phosphite, trilauryl phosphite, tristearyl phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite. Specific examples of such organic phosphite compounds include "ADK STAB (registered trademark; the same applies below) 1178," "ADK STAB 2112," and "ADK STAB HP-10" manufactured by ADEKA Corporation, "JP-351," "JP-360," and "JP-3CP" manufactured by Johoku Chemical Industry Co., Ltd., and "IRGAFOS (registered trademark; the same applies below) 168" manufactured by BASF.
[0041] As the phenol-based antioxidant, a hindered phenol-based antioxidant is preferably used. Specific examples of hindered phenol-based antioxidants include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphate, 4,6-bis(octyl butylthiomethyl)-o-cresol, ethylene bis(oxyethylene) bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, and the like.
[0042] Among them, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate are preferred. Specific examples of such hindered phenol-based antioxidants include "Irganox (registered trademark, the same applies below) 1010" and "Irganox 1076" manufactured by BASF, and "Adeka STAB AO-50" and "Adeka STAB AO-60" manufactured by ADEKA.
[0043] The content of the stabilizer in the resin composition used in this embodiment is usually 0.001 parts by mass or more, preferably 0.005 parts by mass or more, more preferably 0.01 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, more preferably 0.3 parts by mass or less, relative to 100 parts by mass of the (A) polycarbonate resin. By setting the content of the stabilizer within the above range, the effect of adding the stabilizer is more effectively exhibited. The resin composition used in the present embodiment may contain only one type of stabilizer, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.
[0044] <<Release agent>> The resin composition used in this embodiment may contain a release agent. Examples of the release agent include aliphatic carboxylic acids, salts of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, polysiloxane-based silicone oils, ketone waxes, and light amides. Of these, aliphatic carboxylic acids, salts of aliphatic carboxylic acids, and esters of aliphatic carboxylic acids and alcohols are preferred, and salts of aliphatic carboxylic acids are more preferred. For details about the release agent, please refer to the descriptions in paragraphs 0055 to 0061 of JP 2018-095706 A and paragraphs 0106 to 0115 of JP 2015-117298 A, the contents of which are incorporated herein by reference. When the resin composition used in the present embodiment contains a release agent, the content thereof in the resin composition is preferably 0.05 to 3 mass %, more preferably 0.1 to 0.8 mass %, and even more preferably 0.1 to 0.6 mass %. The resin composition used in the present embodiment may contain only one type of release agent, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.
[0045] <Production of Resin Composition> There is no limitation on the method for producing the resin composition used in this embodiment, and a wide variety of known methods for producing resin compositions can be used, including a method in which (A) polycarbonate resin, (B) titanium oxide particles, and (C) phosphate, as well as other components that are added as necessary, are mixed in advance using various mixers such as a tumbler or Henschel mixer, and then melt-kneaded using a mixer such as a Banbury mixer, roll, Brabender, single-screw kneading extruder, twin-screw kneading extruder, kneader, etc. The temperature for melt-kneading is not particularly limited, but is usually in the range of 240 to 320°C.
[0046] <Molded products> The molded article of this embodiment is formed from the pellets used in this embodiment. The pellets described above are molded into a molded article by various molding methods. The shape of the molded article is not particularly limited and can be appropriately selected depending on the use and purpose of the molded article, and examples thereof include film-like, rod-like, cylindrical, annular, circular, elliptical, polygonal, irregular, hollow, frame-like, box-like, panel-like, and button-like shapes.
[0047] The method for forming the molded article is not particularly limited, and a conventionally known molding method can be adopted, for example, injection molding, injection compression molding, extrusion molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating molding) molding, rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, pressure molding, etc. In particular, the resin composition used in this embodiment is suitable for molded articles obtained by injection molding, injection compression molding, and extrusion molding. However, it goes without saying that the resin composition used in this embodiment is not limited to molded articles obtained by these methods.
[0048] The molded article of this embodiment is preferably used for electric and electronic equipment / parts, office automation equipment / parts, information terminal equipment / parts, machine parts, home appliances, vehicle parts, building materials, various containers, leisure goods and sundries, lighting equipment, and the like.
[0049] The reflective member formed from the resin composition used in the present embodiment can be suitably used in the fields of liquid crystal backlight units, various display devices, and lighting devices. Examples of such devices include various mobile terminals such as mobile phones, mobile notebooks, netbooks, slate PCs, tablet PCs, smartphones, and tablet-type terminals, cameras, watches, notebook computers, various displays, and lighting equipment. It is particularly useful as a reflector for liquid crystal display panels, LED (light emitting diode) display panels, and the like. EXAMPLES
[0050] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.
[0051] 1. The following raw materials were used: [Table 1]
[0052] [Table 2]
[0053] The inorganic components in the titanium oxide particles (B) were measured by fluorescent X-rays and calculated in terms of oxides. Specifically, they were evaluated by semi-quantitative measurement. The total of the oxides was taken as 100% by mass, and the proportion of each oxide was expressed in mass%. For the measurements, ZSX Primus manufactured by Rigaku Corporation was used. The results are shown in Table 3. "Other components" refers to the total percentage of oxides other than aluminum oxide, silicon dioxide, and diphosphorus pentoxide. The SiO2 component also includes organic-derived components (especially polyorganosiloxane). [Table 3]
[0054] Examples 1 to 13, Comparative Examples 1 to 12 <Preparation of resin pellets> The components shown in Table 1 or Table 2 were blended in the ratios shown in Tables 4 to 7 (each component is in parts by mass) and mixed in a tumbler for 20 minutes. This mixture was fed to an extruder (TEX30HSST) manufactured by Japan Steel Works, Ltd., kneaded under conditions of a screw rotation speed of 450 rpm, a discharge rate of 30 to 45 kg / hour, and a barrel temperature of 260°C, and extruded into a strand shape. This was cooled with water and pelletized using a pelletizer. However, in Comparative Examples 11 and 12, venting occurred, which resulted in poor productivity and was therefore impractical, so that plate test pieces were not produced and resistance to heat discoloration was not evaluated.
[0055] <Production of Plate Test Pieces> The obtained pellets were dried at 120°C for 5 hours and then injection molded using a steel mold in an injection molding machine (Japan Steel Works, Ltd., "J55AD-6H") under conditions of a cylinder temperature of 280°C, a mold temperature of 80°C, and an injection speed of 100 mm / sec to produce three-stage plate test pieces with thicknesses of 1 mm, 2 mm, and 3 mm.
[0056] <Hue evaluation (heat discoloration resistance)> The plate test piece obtained above was dried in a dryer at 130°C for 1000 hours, and then the color was evaluated. The difference from the initial color was measured as ΔE * It was decided. ΔE * The measurement was carried out by using a color difference meter to measure the hue of the 1 mm thick part of the plate test piece in reflection mode D65 10° field of view, and the L after heat aging was * , a * , b * Measure the initial L * , a * , b * From the difference, ΔE * asked for. ΔE * = [(ΔL* ) 2 +(Δa * ) 2 +(Δb * ) 2 〕 1 / 2 The color difference meter used was the SE6000 type color difference meter manufactured by Nippon Denshoku Industries Co., Ltd.
[0057] [Table 4]
[0058] [Table 5]
[0059] [Table 6]
[0060] [Table 7]
[0061] As is clear from the above results, the molded article formed from the resin composition used in the present embodiment was able to effectively suppress heat modification.
Claims
1. For 100 parts by mass of polycarbonate resin (A), Titanium oxide particles (B) of more than 0.1 parts by mass and not more than 30 parts by mass, Contains 0.005 to 0.5 parts by mass of a phosphate (C); Pellets of a resin composition.
2. 2. The resin composition pellet according to claim 1, wherein the titanium oxide particles (B) contain a silicon-containing compound on the surface thereof.
3. 2. The resin composition pellet according to claim 1, wherein the titanium oxide particles (B) contain organosiloxane on the surface thereof.
4. The resin composition pellet according to claim 1 , wherein the titanium oxide particles (B) contain an aluminum compound on the surface thereof.
5. 2. The resin composition pellet according to claim 1, wherein the titanium oxide particles (B) contain an organosiloxane and an aluminum compound on the surface thereof.
6. The resin composition pellet according to claim 1 , wherein the phosphate (C) comprises an inorganic phosphate.
7. The resin composition pellet according to claim 1 , wherein the phosphate (C) comprises a phosphate having a pH of less than 7.
0.
8. The resin composition pellet according to claim 1 , wherein the phosphate (C) comprises sodium dihydrogen phosphate or / and potassium dihydrogen phosphate.
9. 2. A pellet of a resin composition according to claim 1, wherein the titanium oxide particles (B) contain an organosiloxane and an aluminum compound on the surface thereof, and the phosphate (C) contains sodium dihydrogen phosphate and / or potassium dihydrogen phosphate.
10. A pellet of the resin composition according to any one of claims 1 to 9, which is for use in a light guide plate.
11. A molded article formed from pellets of the resin composition according to any one of claims 1 to 10.
Citation Information
Patent Citations
Aromatic polycarbonate resin composition
JP2000198916A
Polycarbonate resin composition and molding
JP2015059150A